Revision of the Ambrysus pudicus Stål species complex (Heteroptera: Nepomorpha: Naucoridae) with the description of a new species from southern Mexico - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2018)
The Ambrysus pudicus Stål species complex is revised, its species diagnosed, and an illustrated key is presented. The complex includes A. abortus La Rivers, A. amargosus La Rivers, A. funebris La Rivers, A. hungerfordi Usinger, A. parviceps Montandon, A. pudicus Stål, and A. relictus Polhemus & Polhemus. A new species, A. chinanteco, belonging to this complex is described from southern Mexico. The subspecies A. hungerfordi angularis La Rivers, A. h. spicatus La Rivers, and A. h. triunfo La Rivers are herein elevated to full species level and considered members of this species complex. The subspecies A. pudicus barberi Usinger is synonymized with the nominate subspecies. Based on specific combinations of morphological features, two subcomplexes of species are recognized within the complex. The species A. funebris is transferred from the subgenus Acyttarus La Rivers to the subgenus Ambrysus Stål. In order to fix the identity of three species in the complex, neotypes for A. amargosus and A. spicatus and a lectotype for A. pudicus are designated here. The species in the A. pudicus complex are distributed in North America from the southwestern and southern United States to northern Costa Rica. New country records from Central America are presented for A. parviceps and A. pudicus. New state records from Mexico are presented for A. abortus, A. angularis, A. hungerfordi, A. parviceps, A. pudicus, and A. spicatus.